2015
DOI: 10.4236/ajac.2015.62015
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Rapid ESI-MS/MS Method for Quantitative Analysis of Docetaxel in Polymeric Matrices of PLGA and PLGA-PEG Nanoparticles through Direct Injection to Mass Spectrometer

Abstract: Docetaxel is a member of taxan family of antineoplastic agents widely used in cancer chemotherapy. However, application of conventional chemotherapy with commercial formulation has been accompanied with matters of concern regarding drug's biodistribution, pharmacokinetics, and pharmacodynamics. Polymeric nanoparticles have been widely used as unique drug delivery vehicles to circumvent such problems. Docetaxel-loaded poly (lactide-co-glycolide) (PLGA) and poly (lactide-co-glycolide)-poly (ethylene glycol) (PLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…Depending on different experimental conditions, docetaxel and the IS may tend to generate different adducts when ionized through an ESI source. Although there are reports that exploited protonated adduct MRM transitions with good sensitivity 27 , in our studies, spectra revealed that docetaxel formed Na + adducts more easily than H + adducts even in the presence of formic acid. Under ESI + conditions respective precursor ions for docetaxel and the IS were [docetaxel + Na] + at m/z 830.0 and [paclitaxel + Na] + at m/z 876.2 as shown in Fig.…”
Section: Resultscontrasting
confidence: 67%
“…Depending on different experimental conditions, docetaxel and the IS may tend to generate different adducts when ionized through an ESI source. Although there are reports that exploited protonated adduct MRM transitions with good sensitivity 27 , in our studies, spectra revealed that docetaxel formed Na + adducts more easily than H + adducts even in the presence of formic acid. Under ESI + conditions respective precursor ions for docetaxel and the IS were [docetaxel + Na] + at m/z 830.0 and [paclitaxel + Na] + at m/z 876.2 as shown in Fig.…”
Section: Resultscontrasting
confidence: 67%
“…In all these spectra, protonated species [M+H] + common in ESI(+)-MS were absent as it has been similarly reported [16] Although other researchers have confirmed predominant formation of protonated species in such studies [11,13]. Furthermore, Ramaroson-Raonizafinimanana [17] had also observed similar fragmentation of such lipophilic β-diketones as it was found in the mass spectrum of 2,4-diketone silyl ether derivatives described in Figure 6.…”
Section: Table1: Esi-ms(+) Interpretation Of the Htdsupporting
confidence: 75%
“…ESI-MS was also applied successfully for the qualitative analysis of green tea extract [12]. Quantitative analysis of docetaxel in polymeric matrices of poly (lactide-co-glycolide) and poly (lactide-co-glycolide)-poly (ethylene glycol) nanoparticles has been reported using ESI-MS [13]. It was observed that there was more intense formation of [M+H] + than [M+Na] + [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…gas, liquid or solid), an attribute which potentially offers numerous advantages. While other ambient techniques may perform similarly, including direct-injection electrospray ionization (DI-ESI) (19), easy ambient sonic-spray ionization (EASI) (20), and paper spray ionization (PSI) (21), DART-HRMS, which is enjoying increasing use as a sample screening tool for forensic labs, offers extremely fast analysis times and minimal methods development. The approach has been shown to work well for the rapid direct analysis of very complex matrices, including whole botanical samples such as leaves or seeds, extracts, and other plant products (22)(23)(24).…”
Section: Author Manuscriptmentioning
confidence: 99%